Optimizing heat transfer performance in two-phase closed thermosyphons: A novel design and experimental evaluation - Mohammad Khalili; Seyed Alireza Mostafavi; Seyed Mohammad Mousavi; Hossein Moghadamrad (Heliyon)
Effective heat dissipation is crucial in various thermal management applications, including electronics, renewable energy systems, and heating and cooling systems. Two-phase closed thermosyphons (TPCTs) are recognized for their efficient heat transfer and have been widely adopted in these fields. This study presents a novel design for a TPCT that incorporates a unique internal cone-shaped tube at the evaporator. This innovative feature aims to minimize vapor-liquid interaction within the main tube, potentially leading to enhanced heat transfer efficiency. The proposed TPCT is evaluated against a conventional design using water and ethanol as working fluids. Thermal performance is assessed under varying heat inputs (50 W–250 W) and filling ratios (40 %, 55 %, 70 %, 85 %). The results indicate that the optimal filling ratio depends on the working fluid. Water exhibits the best performance at 55 % and 85 % filling ratios, whereas ethanol achieves its optimum at 70 %. Notably, at a 70 % filling ratio with a 50 W heat input, the novel TPCT design exhibits a significant 45.7 % reduction in thermal resistance compared to the conventional design. As expected, increasing heat input reduces thermal resistance but also elevates operating temperatures for both TPCTs. Notably, the novel TPCT demonstrates a significant improvement in thermal performance compared to the conventional design, particularly when using ethanol as the working fluid.